Specific aspects of developing physical qualities of gymnastics aged 8-9 - Dehkanova Mahmuda Artikovna (Genius Publishing Group, 2022)
The complexity of the elements of gymnastics in recent years pays special attention to the development and improvement of physical qualities of young gymnasts. However, frequently the level of development of these qualities does not give chance for the effective mastery of the elements of gymnastics
Keywords: physical and functional opportunities; requirements; gymnastic; combinations